(3eYQaI CfhGY Yde GdMOjK hCUhdgs - (3YKeGf Hf YHO GdQMef (B((3UdGM GdOjf(B) (3GHf YKeGf Hf ehSi Hf CHj GdfUQ GdfUQj GdTgQRhQj GdcQOj GdTQNGfj, CHh YeQh, Jbj GdOjf, GdeYQha HGHf GdUdGM,J (B643 (3g` s ((3eMeO Hf eMeO Hf CMeO Hf YjSi GdCei s)
(3ChdgG (B:s
(3GdMeO ddg GdefGOi ef ESJgOGg , hGdehGbi ef EJbGg gPG hEf Yde GdMOjK ef CaVd GdYdhe GdaGVdI hCfaY Gdafhf GdfGaYI jMHg PchQ GdQLGd haMhdJge s
(3BNQgG (B:s
(3GdMeO Gddge dGeGfY deG CYWjJg hdG eYWi deG efMJ ced cJGH Yde GdMOjK HMeO Gddg hYhfg hGdUdGI GdJGeI Ydi eMeO fHjg hBdg hUMHg s
(3GdfSNI HgG MhGTs
(3fSNI fajSI LOkGs
(3Ydi GdfSNI bQGAGJ JQLY Edi SfJi (B722(3g` , (B730 (3g`s
(3bQf GdfSN (B:s
(3GdbQf GdSGHYs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GdMOjK h GdeUWdMs